Helpless Priming Sends CD8+ T Cells on the Road to Exhaustion - Busselaar, Julia; Tian, Sun; van Eenennaam, Hans; Borst, Jannie (Frontiers in Immunology, 2020)
Persistent antigen exposure in chronic infection and cancer has been proposed to lead to cytotoxic T lymphocyte (CTL) “exhaustion”, i.e. loss of effector function and disease control. Recent work identifies a population of poorly differentiated TCF-1+PD-1+ CD8+ T cells as precursors of the terminally exhausted CTL pool. These “predysfunctional” CTLs are suggested to respond to PD-1 targeted therapy by giving rise to a pool of functional CTLs. Supported by gene expression analyses, we present a model in which lack of CD4+ T-cell help during CD8+ T cell priming results in the formation of predysfunctional CTLs. Our model implicates that predysfunctional CTLs are formed during priming and that the remedy for CTL dysfunction is to provide “help” signals for generation of optimal CTL effectors. We substantiate that this may be achieved by engaging CD4+ T cells in new CD8+ T cell priming, or by combined PD-1 blocking and CD27 agonism with available immunotherapeutic antibodies.